Changements climatiques et mise en tourisme du fleuve St-Laurent au Québec - Dominic Lapointe; Bruno Sarrasin; Alexis Guillemard (VertigO)
The shorelines of the St. Lawrence River are a core touristic attraction in Quebec, but they also represent spaces that will be strongly affected by climate change. This paper is based on a multi-conceptualization of space to analyze the representations embedded in two state discourses : The Tourism Development Strategy for St. Lawrence River and the Climate Change Adaptation Strategy. Thereafter, the paper discusses how actors 'problematize' adaptation to climate change in those two discourses, to better understand the similarities and differences of stakeholder interests, alliances and oppositions to contribute solving implementation problems.